2020
DOI: 10.31681/jetol.777647
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Potential of ICT for Transformative Learning among Youth: A Path to 21st Century Competencies

Abstract: This paper reports the potentials of ICT in enhancing the acquisition of the 21 st Century skills among youth in Higher Learning Institutions (HLIs). Within this broad aim, the paper highlights the possibilities of engaging youth in transformative learning tasks through technology as a necessary pedagogical tool for improving digital competence. The study employed quantitative and qualitative strategies in which both an online survey questionnaire and Focus Group Discussion were used for data collection. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…For this reason, the development of teachers' skills is a situation that should be given great importance. In a study conducted with pre-service teachers, these teachers mentioned that among the things to be done to acquire 21st century skills, they need studies mostly under "information, media and technology skills" and then "21st century support systems", "life and career skills", "learning and renewal skills" and "basic topics and themes" respectively (Erten, 2019;Ndibalema, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…For this reason, the development of teachers' skills is a situation that should be given great importance. In a study conducted with pre-service teachers, these teachers mentioned that among the things to be done to acquire 21st century skills, they need studies mostly under "information, media and technology skills" and then "21st century support systems", "life and career skills", "learning and renewal skills" and "basic topics and themes" respectively (Erten, 2019;Ndibalema, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Collaborative tasks: Collaborative approach is as a key drive towards the acquisition of 21st century skills (Ndibalema, 2020). For that, in the study, an assessment sheet have developed towards the students who learn in collaboration in the 21st-century.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…The results obtained in this context revealed that the digital competencies of learners and teachers should be increased in digital transformation. Similarly, it has been stated that there are changing roles such as autonomy, flexibility, technology use proficiency, and problem-solving skills in learning with digitalization (Ndibalema, 2020;Rejón Guardia et al, 2020).…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%